2010
DOI: 10.1177/1420326x10387694
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation and In Situ Investigation of Fine Particle Dispersion in an Actual Deep Street Canyon in Hong Kong

Abstract: This paper reports a computational fluid dynamics simulation of airflow and fine particle (PM 2.5 ) dispersion in the street canyon in Hong Kong, using large eddy simulation. An aspect ratio (AR) of 2.7 and a Reynolds number of 5 Â 10 6 with a one main vortex, were used. This study focused mainly on the vehicle-induced momentum source and PM 2.5 concentrations were measured at 10 altitudes near the leeward wall in the street canyon, to provide high resolution measurements for model validation. The simulated PM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
53
2
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(59 citation statements)
references
References 44 publications
2
53
2
2
Order By: Relevance
“…The time step in simulations was 0.03s. A self-produced CFD cord was used in our current simulations, which was validated by our previous works (Gu et al, 2010;Zhang et al, 2011). The finite volume method was used to discretize the governing equations and the SIMPLE method was used to solve the discretized equations.…”
Section: Numerical Methods and Modelling Conditionsmentioning
confidence: 99%
See 2 more Smart Citations
“…The time step in simulations was 0.03s. A self-produced CFD cord was used in our current simulations, which was validated by our previous works (Gu et al, 2010;Zhang et al, 2011). The finite volume method was used to discretize the governing equations and the SIMPLE method was used to solve the discretized equations.…”
Section: Numerical Methods and Modelling Conditionsmentioning
confidence: 99%
“…The drag force induced by moving vehicles was added to the additional source term of the governing equation (Zhang et al, 2011), as shown in Eq. (2).…”
Section: Numerical Methods and Modelling Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, the seriously high concentrations of PM 2.5 in ambient air is contributing to the ash haze weather in various cities (Friedlander and Marlow, 1977;Du et al, 2012). Various studies have shown that the mass concentration and chemical compositions of aerosols in each city are very different due to the different urban economic developments, traffic conditions, industrial activities and meteorological factors (Zhang et al, 2011;Zhang and Gu, 2013;Huang et al, 2014;Rohde and Muller, 2015), however, the characteristics of the atmospheric conditions on the formation of haze episodes have not been sufficiently studied.…”
Section: Introductionmentioning
confidence: 99%
“…Atmospheric pollution and urban air quality management: The study of urban air quality management and characterization of urban pollution [15][16][17] and emissions in urban areas and urban dispersion of pollution in street canyons to understand the behaviour of sources, dispersion and their chemical characteristics, [18][19][20] so as to develop urban air quality management strategies to provide guides for urban planning of city centres and urban architecture. 7,21 The development of simulation parameters for dispersion airflow of ambient air pollutants in urban environment is an important achievement for urban air quality management. 22,23 The triboelectric charging of airborne particles under various humidity conditions is a particular highlight of efforts to understand the possible mechanism for explosive growth of PM 2.5 concentration during pollution episode events that is frequently occurring in winter in China.…”
mentioning
confidence: 99%